Pengaruh Variasi Heat Input pada Pengelasan Dissimillar antara Baja ASTM A36 Dan ASTM A131 Terhadap Tensile Strength dan Struktur Makro - Muhammad Musta'in; Khoiruman khoiruman; Heni Siswanti; Arisessy Maharani Mulananda (INOVTEK POLBENG, 2022)
In some structural engineering applications, sometimes necessary to weld two different metals, called dissimilar welding. In the shipbuilding process, the method commonly used for dissimilar welding is FCAW (Flux Cored Arc Welding). Due to the difference in material properties between the two welded metals, the quality of the welded joint needs to be studied. Several things affect the mechanical properties of the dissimilar welded joint, one of them is heat input. To evaluate the dissimilar welded joint strength, it is necessary to carry out mechanical testing. Dissimilar welding of ASTM A36 and ASTM A131 steel with three different heat inputs was analyzed experimentally by tensile test and macrostructure observation. The analysis result shows that the yield stress increases when the heat input increases but then decreases when the heat input continues to be increased up to 60 Kj/mm. The opposite result is shown by the ultimate stress value. However, in all heat input conditions at 22 Kj/mm, 52 Kj/mm, and 60 Kj/mm the yield stress and ultimate stress meet the acceptance criteria. In this study, heat input variation has no significant effect on changes in mechanical strength of dissimilar welding results. The macrostructure observations show that the higher the heat input, the wider the Heat Affected Zone (HAZ) area.